The Gulf Cooperation Council and the Eurasian Economic Union: opportunities and prospects of trade cooperation - P. S. Prokopiev (Вестник университета, 2022)
The article discusses the possibilities of developing trade cooperation between the Eurasian Economic Union and the Cooperation Council for the Arab States of the Gulf. The purpose of the work is to identify and analyse specific sectors of the economy that may offer potential interest in the event of the creation of a free trade zone between integration associations. As a result of the study, potential opportunities for trade and economic cooperation in the agro-industrial complex were identified. The methods of analysis and comparison of data from information and analytical materials on the advantages and trends of foreign trade relations of the EAEU and GCC countries were used. The state of the matter at the political level is indicated, as well as the main barriers and potential risks to the growth of trade. The relevance of the work lies in the need to diversify foreign trade partners and ensure the sustainability of economic growth for the integration associations under consideration in the conditions of macroeconomic turbulence, global disruption of supply chains and the general degree of high tension in international economic relations.